Augmenting the VLE using widget technologies. (1st January 2011) - Wilson, Scott; Sharples, Paul; Griffiths, Dai; Popat, Kris
Can widget technologies revolutionise the virtual learning environment (VLE) and challenge the dominant design of e-learning? Are widgets ready to be deployed in today's VLEs? The authors describe an experimental implementation of the Moodle VLE using the W3C widget specification and Google Wave Gadget API to replace existing core features. This raises four challenges: The paper also describes further work in adding widget technology to other VLEs using the IMS Basic learning tools interoperability (LTI) specification.